Fenomena drop out tingkat SMA se-kota Banda Aceh - Rizki Surya Ananda; Dahliana Abd; Nurbaity Bustamam (Program Studi Bimbingan dan Konseling, FKIP Universitas Syiah Kuala, 2019)
Abstract: Drop outs are forced out of school before completing the overall learning. Descriptive research method with a qualitative approach. The research subjects consisted of 4 principals, 1 vice principal, 1 student field and 8 BK teachers in nine high school level throughout Banda Aceh. Data collection techniques using interview methods and documentation. Data analysis using qualitative descriptive. The results showed the number of students dropping out during the last 3 years reached 44 students. Caused by internal factors, namely not going up to class, low interest in learning, students not attending school, feeling inferior and violating school rules. Like smoking and jumping fences, fighting teachers, leaving school without permission and taking the rights of others (stealing). The external factors are fighting, the circulation of immoral videos, dating and watching immoral videos in schools and being involved in drug use. While the handling procedures are preventive measures, including the principal's policy. Like meetings with student guardians and make observations on teacher performance. Handling from BK counselors such as individual and group counseling, as well as providing case notebooks and student pocket books. The guidance step is in the form of handlers from study teachers, homeroom teachers, BK teachers, student fields and principals. As well as follow-up steps, namely the existence of a special meeting of principals with homeroom teachers, BK teachers, student fields and guardians of students to make decisions and recommend secondary schools. It is expected that the school will work together in following up on each problem in accordance with the established procedures. For the next researcher, they can do more in-depth research about the phenomenon of drop outKeywords: Drop out phenomenon, cause of drop out, drop out handling procedure.Abstrak: Drop out adalah dikeluarkan dari sekolah secara terpaksa sebelum menyelesaikan pembelajaran secara keseluruhan. Metode penelitian deskriptif dengan pendekatan kualitatif. Subjek penelitian terdiri dari 4 orang kepala sekolah, 1 wakil kepala sekolah, 1 bidang kesiswaan dan 8 guru BK di sembilan sekolah tingkat SMA Se-kota Banda Aceh. Teknik pengumpulan data menggunakan metode wawancara dan dokumentasi. Analisis data menggunakan deskriptif kualitatif. Hasil penelitian menunjukkan jumlah siswa drop out selama 3 tahun terakhir mencapai 44 orang siswa. Disebabkan oleh faktor internal yaitu tidak naik kelas, minat belajar rendah, siswa tidak hadir ke sekolah, rasa minder dan melanggar peraturan sekolah. Seperti merokok dan lompat pagar, melawan guru, keluar sekolah tanpa izin serta mengambil hak orang lain (mencuri). Adapun faktor eksternal yaitu perkelahian, beredarnya video asusila, berpacaran dan menonton video asusila di sekolah serta terlibat pemakaian obat terlarang (narkoba). Sedangkan prosedur penanganannya yaitu langkah preventif meliputi, kebijakan kepala sekolah. Seperti rapat dengan wali murid dan melakukan observasi terhadap kinerja guru. Penanganan dari guru BK seperti, konseling individual dan kelompok, serta menyediakan buku catatan kasus dan buku saku siswa. Langkah pembinaan berupa penangan dari guru bidang studi, wali kelas, guru BK, bidang kesiswaan dan kepala sekolah. Serta langkah tindak lanjut yaitu adanya rapat khusus kepala sekolah dengan wali kelas, guru BK, bidang kesiswaan dan wali murid untuk mengambil keputusan serta merekomendasi sekolah lanjutan. Diharapkan kepada pihak sekolah untuk saling berkerja sama dalam menindak lanjuti setiap masalah sesuai dengan prosedur yang ditetapkan. Bagi peneliti selanjutnya dapat melakukan penelitian lebih mendalam mengenai fenomena drop outKata kunci: Fenomena Drop Out, Penyebab Drop Out, Prosedur Penangan Drop 0ut.